In Situ Investigation of Methane Dry Reforming on Metal/Ceria(111) Surfaces: Metal–Support Interactions and C−H Bond Activation at Low Temperature. (5th September 2017) - Liu, Zongyuan; Lustemberg, Pablo; Gutiérrez, Ramón A.; Carey, John J.; Palomino, Robert M.; Vorokhta, Mykhailo; Grinter, David C.; Ramírez, Pedro J.; Matolín, Vladimír; Nolan, Michael; Ganduglia‐Pirovano, M. Verónica; Senanayake, Sanjaya D.; et al.
Abstract: Studies with a series of metal/ceria(111) (metal=Co, Ni, Cu; ceria=CeO2 ) surfaces indicate that metal–oxide interactions can play a very important role for the activation of methane and its reforming with CO2 at relatively low temperatures (600–700 K). Among the systems examined, Co/CeO2 (111) exhibits the best performance and Cu/CeO2 (111) has negligible activity. Experiments using ambient pressure X‐ray photoelectron spectroscopy indicate that methane dissociates on Co/CeO2 (111) at temperatures as low as 300 K—generating CH x and CO x species on the catalyst surface. The results of density functional calculations show a reduction in the methane activation barrier from 1.07 eV on Co(0001) to 0.87 eV on Co 2+ /CeO2 (111), and to only 0.05 eV on Co 0 /CeO2− x (111). At 700 K, under methane dry reforming conditions, CO2 dissociates on the oxide surface and a catalytic cycle is established without coke deposition. A significant part of the CH x formed on the Co 0 /CeO2− x (111) catalyst recombines to yield ethane or ethylene.